Peran Zakat, Infaq, Shadaqah dan Wakaf dalam Memberdayakan Ekonomi Ummat - Cut Mutia Muqhniy; Sarah Aulia; Andriyani Andriyani; Muhammad Labib; Wahdi Sayuti (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The background of this research is based on the enormous potential of zakat, infaq, shadaqah, and waqf (ZISWAF) as Islamic social finance instruments which, if managed optimally and sustainably, can play a significant role in reducing poverty and promoting comprehensive economic independence among communities amid the ongoing challenges of social inequality. The purpose of this study is to explain the strategic function of ZISWAF in strengthening the community’s economy while emphasizing the urgency of professional, transparent, and targeted management for the improvement of public welfare at large. The research method used was library research, evaluating various literature sources such as books, scientific journals, and relevant previous research reports. The collected data was then analyzed using a qualitative descriptive approach to provide an in-depth understanding of the mechanism of economic empowerment through ZISWAF. Research findings show that ZISWAF plays a crucial role in improving economic welfare through a paradigm shift from consumptive assistance to productive assistance programs. Management oriented towards sustainability and transparency has proven effective in promoting economic ind ependence among low-income communities and significantly reducing poverty rates. The implication of this study confirm that strengthening regulations, digitizing management, and improving public literacy regarding ZISWAF are essential. Management institutions must continue to improve their accountability in order to increase public trust, so that ZISWAF can become a key development in the future.